Liver Injury after Selective Androgen Receptor Modulator Intake: A Case Report and Review of the Literature - Mertens, Jonas E.; Bömmer, M. Till C.; Regier, Manuel B.; Gabriëls, Gert; Pavenstädt, Hermann; Grünewald, Inga; Horvath, Judit; Trebicka, Jonel; Schmidt, Hartmut; Schlevogt, Bernhard (Zeitschrift für Gastroenterologie, 2023)
Liver injury associated with selective androgen receptor modulators (SARMs) is an issue that has not been reported often. We report a case of a previously healthy 24-year-old male, who was referred to our hospital for severe jaundice with intense pruritus. He had previously taken the SARM Enobosarm (also known as Ostarine) for muscle-building purposes. Blood serum levels of total bilirubin exceeded 30 mg/dL with only a slight elevation of liver enzymes. Liver biopsy revealed isolated hepatocellular cholestasis (bland cholestasis) with limited inflammation or necrosis. Supportive treatment was begun in our hospital with molecular adsorbent recirculation system (MARS) albumin dialysis, as well as cholestyramine for pruritus relief. During therapy, bilirubin levels and symptoms regressed, and after five sessions of dialysis, the patient could be released from our clinic in a markedly improved clinical and laboratory condition. However, bilirubin parameters regressed slowly after this, reaching normal levels as late as six months after first intake of the compound. Exome-based genetic testing brought about no pathogenic variants for cholestatic liver disease in our patient. Nevertheless, three common heterozygous polymorphisms associated with an increased risk for intrahepatic cholestasis could be identified. Our case demonstrates that SARMs can cause severe liver injuries not prominently mentioned in safety data sheets. Therefore, these compounds constitute a potential danger to the user’s health. This holds especially true when taking SARMs without supervision by a medical professional, which should consist of a thorough monitoring of liver enzyme and bilirubin levels.
Keywords: Ostarine; Drug-induced liver injury; DILI; Cholestasis; SARM; Enobosarm; Anabolic androgenic steroids